VD_FINDINFO Décision / 2012 / 60 vom 12. September 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, VOLONTÉ DE RECOURIR, RADIATION DU RÔLE | 319 CPP (CH), 352 CPP (CH), 393 al. 1 let. a CPP (CH), 395 let. a CPP (CH)